Role of cricothyrotomy and percutaneous tracheostomy in airway management - Mat Nor, Mohd. Basri (2012)
Since Ciaglia et al described the percutaneous dilational tracheostomy in 1985, PDT has gained popularity over surgical tracheostomy in the intensive care setting. Percutaneous tracheostomy (PCT) requires less time to perform, it is less expensive and its typically performed sooner. In a meta-analysis of 17 randomized control trials, PDT offers several advantages such as decreased wound infections, decreased bleeding and mortality compared to surgical technique. Indications for PCT are the same as those for standard open tracheostomy. Established contraindications against PCT are unstable fractures of cervical spine, severe local infection of anterior neck and uncontrolled coagulopathy. Relative contraindications are high PEEP or oxygen requirements, difficult anatomy, proximity to extensive burns or surgical wounds, elevated ICP, hemodynamic instability and previous radiotherapy to the neck. In experienced hands, PDT seems to be a safe procedure. The number of relative contraindications to PDT declines with increasing operator experience. Overweight patients have a five times higher risk of perioperative complications with PDT than normal weight patients.